Shipborne anti-collision sounding system optimization based on ACT algorithm and Internet of things - Zhu, Yuye; Bi, Yanliang; Su, Xiaomin; Kouritzin, C.M. (Journal of intelligent & fuzzy systems, 2018)
For the current shipborne anti-collision sounding system, when multiple detection signals are transmitted, it is difficult to avoid collision with each other. In addition, there are shortcomings of insufficient energy consumption, low sounding precision, and slow response. To address this problem, a shipborne anti-collision sounding system based on ACT algorithm and Internet of things is designed in this paper. With ZigBee wireless communication technology and embedded technology, the function of anti-collision and sounding is realized by modular design. For the problem of the signal collision of each node of the wireless network, the ACT algorithm is introduced for system optimization to prevent signals from conflict when receiving, and ensure the synchronization and accuracy of the whole system. STM32F103 VET6 embedded chip is used as the control core of the system. CC2530 is responsible for the implementation of ZigBee wireless network communication. Experimental results show that the designed system has the advantages of low energy consumption, fast response, and high precision.